UNDERSTANDING THE RARE BONE TUMOR ADAMANTINOMA - Sahito, Badaruddin; Jatoi, Nadia Nazir; Kumar, Dileep; Asad, Ameema; Hasan, Syed Saboor; Ali, Maratib (Journal of Ayub Medical College Abbottabad, 2021)
Adamantinoma is a rare neoplastic bone tumor that has the potential to metastasize. The classic presentation is in the tibial region however; cases involving other bones of the body have been noticed. The tumour is very likely to be mistaken for other bone diseases and therefore it is important to investigate and study about its nature and thus differentiate it from other differentials. Nevertheless, literature on the presentation, findings, investigations and treatment options of adamantinomas are limited. In this case series, we report four cases from a local hospital in Karachi who were diagnosed, treated and followed up for adamantinoma. Studies regarding the disease will help us understand more about its features.